A comparison of different doses of gabapentin to attenuate the haemodynamic response to laryngoscopy and tracheal intubation in normotensive patients - Usha Bafna; Vipin K Goyal; Ashish Garg (Wolters Kluwer Medknow Publications, 2011)
Background: Laryngoscopy and intubation evokes a transient but marked sympathetic response manifesting as increase in heart rate, blood pressure & arrhythmias. We conducted a study to compare the effect of different doses of gabapentin on hemodynamics associated with laryngoscopy and intubation. Patients & Methods: Ninety normotensive patients (ASA I and II) between 20-60 years undergoing elective surgery requiring intubation were randomly allocated into three groups of 30 patients each. Group I received oral placebo, Group II received 600 mg of gabapentin and Group III received1000 mg of gabapentin, with sip of water 1 h prior to surgery in the operation theatre. Patients were premedicated with Glycopyrrolate, midazolam and fentanyl and induction was done with thiopentone sodium and succinylcholine. Heart rate, systolic, diastolic and mean arterial pressure were recorded at baseline, 0, 1, 3, 5 and 10 min after intubation. Results: MAP and HR were significantly increased in patients receiving placebo and 600 mg gabapentin after laryngoscopy and intubation compared to baseline value and Group III. Significant decrease in MAP was seen just after intubation, 1, 3, 5 and 10 min after (P < 0.001, P < 0.001, P < 0.05, P < 0.05 and P < 0.05 respectively) in Group III compared to Groups I and II. HR was significantly decreased within 10 min of intubation (P<0.001)) in Group III compared to Groups I and II. Conclusion: Gabapentin1000 mg given 1 h before operation significantly attenuated the haemodynamic response to laryngoscopy and intubation in normotensive patients.